2017
DOI: 10.1186/s12913-017-2379-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumer and clinician preferences and decision making for rehabilitation following arthroplasty in the private sector

Abstract: BackgroundTo understand private consumer and clinician preferences towards different rehabilitation modes following knee or hip arthroplasty, and identify factors which influence the chosen rehabilitation pathway.MethodsMixed methods cross-sectional study involving 95 semi-structured interviews of consumers (patients and carers) and clinicians (arthroplasty surgeons, physiotherapists and rehabilitation physicians) in Sydney, Australia, during 2014–2015. Participants were asked about the acceptability of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…At least one participant in our sample strongly believed that recovery at home was unsafe and that inpatient rehabilitation would aid their recovery. In an Australian study exploring the acceptability of different modes of rehabilitation, Buhagiar et al 31 also found that positive past experiences and beliefs about level of support influenced patients' rehabilitation preferences. Preoperative screening of patients' beliefs and expectations about in‐hospital versus at‐home recovery may identify patients for whom a short‐stay care pathway may be unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…At least one participant in our sample strongly believed that recovery at home was unsafe and that inpatient rehabilitation would aid their recovery. In an Australian study exploring the acceptability of different modes of rehabilitation, Buhagiar et al 31 also found that positive past experiences and beliefs about level of support influenced patients' rehabilitation preferences. Preoperative screening of patients' beliefs and expectations about in‐hospital versus at‐home recovery may identify patients for whom a short‐stay care pathway may be unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…However, a range of patient and provider-based factors have been recognised as affecting the rehabilitation pathway chosen by patients, such as preoperative preferences, previous experiences, perceived benefits, clinical status post-surgery, as well as insurance provider and hospital business model. 51 This association needs clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Private patients are free to choose this pathway, whilst public patients are not. Previous research suggests choice in the private sector is influenced by several factors including the patient's perceived efficacy of the pathway and their sense of entitlement owing to their private health insurance, as well as by surgeon preference and site‐specific (hospital/clinician) behaviours or factors 17,27 . Investigating referral to inpatient rehabilitation using privately insured cohorts, therefore, is confounded by patient preference 23,28 .…”
Section: Introductionmentioning
confidence: 99%